2016
DOI: 10.1002/ecs2.1284
|View full text |Cite
|
Sign up to set email alerts
|

In an arid urban matrix, fragment size predicts access to frugivory and rain necessary for plant population persistence

Abstract: Cities annex wilderness and alter the interactions between the plant and animal assemblages embedded in the remaining nature fragments. Here, we explore consequences of habitat fragmentation for dispersal of cactus by fruit‐eating mammals in the Sonoran Desert landscape. We use the barrel cactus, Ferocactus wislizeni, as a model system to diagnose (1) how fruit utilization by a mammal assemblage changes with fragment area and isolation, (2) what characteristics make individual plants particularly susceptible t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 98 publications
0
6
0
Order By: Relevance
“…Forests with fewer zoochoric plants offer fewer resources to vertebrates (Terborgh et al 2008 ), affecting their survival, growth, and reproduction, contributing to fragments’ defaunation. The diminishing vertebrate’s biomass affects the quantity and quality of seed dispersal (e.g., empty forest process by Redford 1992 ) (Ness et al 2016 ) and the soil’s fertilization through urine and feces (Feeley and Terborgh 2005 ). Less fertilization reverberates back into plant communities, decreasing rates of the establishment of new adults.…”
Section: Introductionmentioning
confidence: 99%
“…Forests with fewer zoochoric plants offer fewer resources to vertebrates (Terborgh et al 2008 ), affecting their survival, growth, and reproduction, contributing to fragments’ defaunation. The diminishing vertebrate’s biomass affects the quantity and quality of seed dispersal (e.g., empty forest process by Redford 1992 ) (Ness et al 2016 ) and the soil’s fertilization through urine and feces (Feeley and Terborgh 2005 ). Less fertilization reverberates back into plant communities, decreasing rates of the establishment of new adults.…”
Section: Introductionmentioning
confidence: 99%
“…We found intermediate removal rates for cosmopolitan species, such as D. viscosa and P. icosandra , but the lowest rate of removal was to introduce specie S. mole . Cities need to be understood within the context of their species interactions [40], because the disruption of interactions between legitimate seed dispersers (mutualist) with plants, beside by the introduction of exotic or cosmopolitan plant species [41] can lead to in the long term to homogeneous species assemblages and local extinctions [34,42]. Overall, our results suggest that both mutualistic– antagonist (i.e., seed disperser and predator) interactions still working in green areas of the city, particularly the interaction with native plants, likely because native species tend to established stronger interactions than introduced species [43].…”
Section: Discussionmentioning
confidence: 99%
“…Lyomis irroratus) [57]. In addition, is necessary to evaluate the contribution of vertebrate species in the process of primary removal in scrublands, as the mammal Bassariscus astutus (Lichtenstein, 1830), which is a very abundant frugivorous species in CDMX [58,59] and their interactions with plant species that have fleshy fruits (e.g., P. icosandra) that could increase the possibility that will colonize new environments (Ness et al, 2016). Fill these gaps, would provide a more complete picture of seed dispersion by the different actors and their threats inside the city.…”
Section: Discussionmentioning
confidence: 99%
“…areas (Fey et al, 2016; that roads restrict animal movements enhancing the fragmentation and isolation of urban green patches, and further delineating the habitat mosaic. Smaller, more isolated, fragments tend to support fewer animal disperser species and smaller population sizes in urban areas (Srbek-Araujo et al, 2017), leading to lower fruit removal rates, as found for cactus fruit removal rates by mammals (Ness et al, 2016). If small, isolated fragments are avoided by animals, it is also likely that seed influx into isolated fragments may decline, eventually leading to local extirpation of certain plant species.…”
Section: Urban Disturbance and Fragmentation May Disrupt Seed Movemenmentioning
confidence: 98%